Effect of Modified Bow Learning on Archery Accuracy in Elementary School Extracurricular - Rizal Cahya Dwiputra; Mugiyo Hartono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study analyzed the effect of archery learning using modified bows on students' accuracy in extracurricular activities at Public Elementary School 02 Pakintelan. Elementary school archery often faces obstacles such as limited facilities, low motivation, and standard equipment unsuited to students' physical characteristics. Modified bows were used as an innovative approach to improve accuracy and engagement. This study used a quantitative quasi experimental one group pretest posttest design with 22 students selected through total sampling Data were collected using an archery accuracy test at 10 meters with 20 shots (maximum score 200). The treatment comprised 16 meetings using modified bows. Data were analyzed using descriptive statistics, normality and homogeneity tests, and a paired-samples t-test (a = 0.05). Results showed significant improvement in archery accuracy after treatment. The mean score increased from 63.95 to 120.86. The paired-samples t-test yielded p=0.000 (p<0.05), indicating a significant effect of modified bow learning on accuracy. In conclusion, modified bows can be recommended as an innovative and effective strategy to improve archery accuracy and student participation in elementary school extracurricular activities.